The Interference of The Indonesian Language in The Daily Arabic Conversation Among Female Students at an Islamic High School in Indonesia: تداخل اللغة الإندونيسية على المحادثة العربية اليومية لدى الطالبات بمدرسة الثانوية الإسلامية بإندونيسيا - Insani, Nurul; Kasih, Baiq Widia Nita (Institut Agama Islam Negeri Palangka Raya, 2025)
Interference is the process of language transfer, where elements from the mother tongue (first language) are integrated into the second language (target language). This research aims to determine (1) the forms of Indonesian language interference in daily Arabic conversations among female students at Madrasah Aliyah Islamiyah Nurul Haramain NWDI Narmada, West Lombok, and (2) the factors causing Indonesian language interference in these daily conversations. A qualitative research approach using the case study method was employed, with data collection techniques including observation, interviews, and documentation. The findings of this study indicate that (1) two types of language interference occur among the female students: syntactic interference and phonological interference, and (2) five factors contribute to the Indonesian language interference in daily Arabic conversations, including (1) difficulties in understanding language grammar, (2) limited vocabulary memorization, (3) lack of awareness in using the target language, (4) teaching methods in the classroom, and (5) beginners in learning Arabic.